2017
DOI: 10.1016/j.jbi.2017.05.011
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of gamification in e-Health

Abstract: Gamification is a relatively new trend that focuses on applying game mechanics to non-game contexts in order to engage audiences and to inject a little fun into mundane activities besides generating motivational and cognitive benefits. While many fields such as Business, Marketing and e-Learning have taken advantage of the potential of gamification, the digital healthcare domain has also started to exploit this emerging trend. This paper aims to summarize the current knowledge regarding gamified e-Health appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
513
0
27

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 777 publications
(641 citation statements)
references
References 45 publications
13
513
0
27
Order By: Relevance
“…"Development and Accomplishment" was the most chosen option for both groups. This finding is in line with the findings of a systematic review of gamification in e-Health [24] who found that the gamification elements that were most often used were "feedback, rewards, progression and social features". Another key outcome was that members and non-members need to be motivated differently.…”
Section: If You Exercise Why Do You Exercise? If Not Why Don't You supporting
confidence: 89%
“…"Development and Accomplishment" was the most chosen option for both groups. This finding is in line with the findings of a systematic review of gamification in e-Health [24] who found that the gamification elements that were most often used were "feedback, rewards, progression and social features". Another key outcome was that members and non-members need to be motivated differently.…”
Section: If You Exercise Why Do You Exercise? If Not Why Don't You supporting
confidence: 89%
“…We suggest that different measures could be applied to the two groups. For example, an app including questionnaires, push reminders to fill them in, and elements of gamification (applying game mechanics to non-game contexts in order to keep participants engaged [26]) might prevent passive discontinuation, but not active withdrawal. Too intrusive reminders could even stimulate withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…It can give citizens more control over their well-being and health, empower health professionals and adolescents, and support the development of new treatments (Calvillo et al, 2015;Karlsson et al, 2014). The digital revolution in health may improve and provide safer, better, and sustainable care (Sardi, Idri, & Fernández-Alemán, 2017;Turner et al, 2015), changing the way the people relates to health professionals and get information on health. study evaluates the effectiveness of an mHealth intervention (TeenPower) specifically designed for adolescents.…”
Section: The Citizens' Health Empowerment By Technology (E-empowerment)mentioning
confidence: 99%